Integration of Design Thinking and Scrum in Development of Retail Marketplace Website - Ivan Naufal Islami Al-Faridzqi; Eko Darwiyanto; Jati Hiliamsyah Husen (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In traditional retail, change and adaptation are necessary for existing developments not to be left behind. In Indonesia, Usaha Kecil Menengah (UKM) can adapt to the help of technological developments. The development in UKM occurs about 12%. Based on these problems, the development of marketplace websites is aimed at UKM businesses marketing their products by utilizing technology. The software development process is needed to develop a website marketplace that suits the market and user needs. Therefore, this study applies design thinking integrated with scrum in the development of website marketplace for retail aims to understand the influence and usefulness of integration in the software development process. The usability measurement with the metric system usability scale (SUS) obtained an average value from SUS of 71.5. The average performance velocity of the team got an average value of 14 points which means in one sprint. Team can ideally complete the point by the average of those points. It can be concluded that design thinking and scrum can be the right combination to create a product based on existing problems by finding the right solution and realizing the solution quickly.